2012
DOI: 10.17221/8/2011-rae
|View full text |Cite
|
Sign up to set email alerts
|

Study and determination of energy consumption to produce conventional rice of the Guilan province

Abstract: Alipour A., Veisi H., Darijani F., Mirbagheri B., Behbahani A.G., 2012. Study and determination of energy consumption to produce conventional rice of the Guilan province. Res. Agr. Eng., 58: 99-106.The aim of this study was to determine the energy efficiency indices in the agro-ecosystems of the Guilan province in 2010. One hundred and twenty-seven farmers were interviewed using a particularly designed questionnaire. The inputs in the calculation of energy use in agro-ecosystems embraced labour, machinery, ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
2
14
1
Order By: Relevance
“…This index is lower and could be as a result of inefficient use of some energy inputs due to inefficient irrigation system. This finding compares closely to Alipour et al (2012) that rice energy ratio in Guilan province of Iran was 2.19 lower than 6.7 rice energy ratio index estimated in Australia by Khan et al (2010). As rice farm practices in Jere Bowl in Nigeria and Guilan province in Iran are considerably not modernized and efficient as in Australia.…”
Section: Energy Ratiosupporting
confidence: 88%
“…This index is lower and could be as a result of inefficient use of some energy inputs due to inefficient irrigation system. This finding compares closely to Alipour et al (2012) that rice energy ratio in Guilan province of Iran was 2.19 lower than 6.7 rice energy ratio index estimated in Australia by Khan et al (2010). As rice farm practices in Jere Bowl in Nigeria and Guilan province in Iran are considerably not modernized and efficient as in Australia.…”
Section: Energy Ratiosupporting
confidence: 88%
“…Other related studies include Dazhong and Pimentel (1984) in China, Singh and Singh (1992) in India, Hulsbergen et al (2001) in Germany, Bockari-Gevao et al (2005) in Malaysia, Khan et al (2010) in Australia, Pracha and Volk (2011) in Pakistan. Cherati et al (2011) and Alipour et al (2012) in Iran.…”
Section: Introductionmentioning
confidence: 98%
“…However, the DSR crop was grown under rainfed condition, so no external irrigation was supplemented. For comparison in the literature, Alipour [39] also reported higher irrigation energy in rice production, and another study on the rice production system in India revealed that irrigation and fertilizers have a higher share of energy input [35]. In addition, in another study, the amount of energy inputs consumed in different rice-based cropping systems were reported to be 44-54% for chemical fertilizers and 11-14% of for in India [40].…”
Section: Energy Balancementioning
confidence: 94%